Succession of Bacterial Community During the Initial Aerobic, Intense Fermentation, and Stable Phases of Whole-Plant Corn Silages Treated With Lactic Acid Bacteria Suspensions Prepared From Other Silages - Sun, Lin; Bai, Chunsheng; Xu, Haiwen; Na, Na; Jiang, Yun; Yin, Guomei; Liu, Sibo; Xue, Yanlin (Frontiers in Microbiology, 2021)
The present study was to investigate the bacterial community in lactic acid bacteria (LAB) suspensions prepared from whole-plant corn silage (LAB suspension-CS) and Elymus sibiricus silage (LAB suspension-ES), and the bacterial community succession of whole-plant corn silages inoculated with LAB suspension-CS or LAB suspension-ES during initial aerobic phase, intense fermentation phase, and stable phase. The LAB suspensions were cultured in sterile Man, Rogosa, Sharpe broth at 37 °C for 24 h and used as inoculants for ensiling. The chopped whole-plant corn was treated with distilled water (CK), LAB suspension-CS (CSL) or LAB suspension-ES (ESL), and then ensiled in vacuum-sealed plastic bags containing 500 g of fresh forage. Silages were sampled at 0 h, anaerobic state (A), 3 h, 5 h, 10 h, 24 h, 2 d, 3 d, 10 d, 30 d, and 60 d of ensiling with four replicates for each treatment. The results showed that Lactobacillus, Weissella and Lachnoclostridium_5 dominated the bacterial community in LAB suspension-CS; Lactobacillus was the most predominant bacterial genus in LAB suspension-ES. During the initial aerobic phase (from 0 h to A) of whole-plant corn silage, the pH and the abundances of Pantoea, Klebsiella, Rahnella, Erwinia and Serratia increased. During the intense fermentation phase (from A to 3 d), the pH decreased rapidly, and the microbial counts increased exponentially; the most predominant bacterial genus shifted from Pantoea to Weissella, and then to Lactobacillus; inoculating LAB suspensions promoted the bacterial succession and the fermentation process, LAB suspension-CS was more effective than LAB suspension-ES. During the stable phase (from 3 d to 60 d), the pH and the microbial counts decreased, and Lactobacillus dominated the bacterial community with a little decrease. The results also confirmed the existence of LAB fermentation relay during fermentation process, which was reflected by Weissella, Lactococcus, and Leuconostoc in the first 5 h, Weissella, Lactococcus, Leuconostoc, Lactobacillus, and Pediococcus between 5 h and 24 h, and Lactobacillus from 24 h to 60 d.